PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN KETERAMPILAN MENULIS TEKS IKLAN PADA SISWA KELAS VIII C SMP SLUB SARASWATI 1 DENPASAR TAHUN PELAJARAN 2024/2025 - Samun, Maria Trinildis; Erawan, Dewa Gede Bambang; Wedasuwari, Ida Ayu Made (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2025)
This research is classroom action research (PTK) which aims to (1) find out the application of the PjBL (Project Based Learning) learning model to improve advertising text writing skills in students in class VIII C SMP SLUB Saraswati 1 Denpasar for the 2024/2025 academic year, (2) find out Steps for Implementing the Project Based Learning Model to Improve Advertising Text Writing Skills in Class VIII C Students of SMP SLUB Saraswati 1 Denpasar Academic Year 2024/2025. Data collection uses observation,tests and documentation. The data obtained was then analyzed descriptively qualitatively and quantitatively. The research results show that the application of the PjBL (Project Based Learning) model is to improve advertising text writing skills in class VIII C students at SMP Slub Saraswati 1 Denpasar. Increased student activity can be seen from students' enthusiasm in responding to learning. Students who are active in learning in class are able to understand the material and complete the three tasks given. Furthermore, if we look at student learning outcomes, the improvement in advertising text writing results can be seen from the assignments given by educators to students and can be seen from the students' average test scores. In the pre-test stage students got an average score of 39.10, in cycle I 61.07 and in cycle II students got an average score of 90. This can be seen from students who were able to put together appropriate titles, appropriate content, appropriate usage. language, suitability of writing, mechanics in students about writing advertising texts. Abstrak Penelitian ini merupakan penelitian tindakan kelas (PTK) yang bertujuan (1) mengetahui Penerapan Model Pembelajaran PjBL (Project Based Learning) Untuk Meningkatkan Keterampilan Menulis Teks Iklan Pada Siswa Kelas VIII C SMP SLUB Saraswati 1 Denpasar Tahun Pelajaran 2024/2025, (2)Mengetahui langkah-langkah Penerapan Model Pembelajran Project Based Learning Untuk Meningkatkan Keterampilan menulis Teks Iklan Pada Siswa Kelas VIII C SMP SLUB Saraswati 1 Denpasar Tahun Pelajaran 2024/2025. Pengumpulan data menggunakan Observasi,Tes dan dokumentasi. Data yang diperoleh kemudian dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil Penelitian Menunjukkan Bahwa Penerapan Model PjBL (Pembelajaran Project Based Learning) Untuk Meningkatkan Keterampilan Menulis Teks Iklan Pada Siswa Kelas VIII C SMP Slub Saraswati 1 Denpasar. Meningkatnya Aktivitas Siswa tampak dari keantusiasan siswa dalam merespon pembelajaran. Siswa aktif dalam pembelajran dikelas mampu memahami materi serta menyelesaikan tiga yang diberikan. Selanjutnya, Jika ditinjau dari hasil belajar siswa, Peningkatan hasil menulis teks iklan terlihat dari penugasan yang diberikan oleh pendidik kepada siswa dan dapat ditinjau dari nilai rata-rata tes siswa. Pada tahap Pre-tes siswa memperoleh nilai rata-rata 39,10 , Pada siklus I 61,07 dan pada siklus II siswa memperoleh nilai rata-rata 90. Hal tersebut dapat terlihat dari siswa yang mampu merangkai keseuaian judul, Keseuaian isi, Ketepatan penggunaan bahasa, kesesuaian tulisan, mekanik pada siswa tentang menulis teks iklan.